Finnish adolescents' perceptions of their health choices: A qualitative study - Moilanen Tanja; Rahkonen Nina; Kangasniemi Mari (WILEY, 2022)
This study described adolescents' perceptions of the aims of their daily health choices and how they make them. We used a qualitative, explorative design, with 67 adolescents aged 15-16 years taking part in semi-structured focus groups in Finland in 2016. We analyzed the data with qualitative inductive content analysis. Adolescents perceived their health choices as automatic and driven by knowledge and mistakes, and these decisions reflected their values and feelings. Their health choices were based on immediate and long-term goals and they reported that making good choices improved their self-confidence and enhanced their individuality. Adolescents also used health choices to promote other people's health. Health choices were linked to parental help and restrictions, and seeking acceptance from friends. Adolescents' health choices were also enabled and limited by society and the environment that they lived in. In conclusion, adolescents' health choices were an integral part of their daily decision-making, reflected the environment they lived in, and aimed to promote their health and express their individuality.